Improvement Of Nahwu And Sharaf Learning Using Amtsilati Method - Huda, Mokhammad Miftakhul; Rais, Pandi; Surur, Agus Miftakhus; Rohmawati, Ati’ (Ijaz Arabi Journal of Arabic Learning, 2020)
Islamic boarding school (pesantren) as traditional Islamic education institution is an invaluable part of the Indonesian national education system, which established by the ulama, the education system aims to teach Islamic lessons. Many classic books in this Islamic boarding are learnt through reading and studying based on amtsilati method. Therefore, this article is intended to investigate learning nahwu shorf, efforts and motivation of students in improving student learning of Nahwu Sharaf in Sunan Ampel Islamic Boarding School using the amtsilati method. In this case, qualitative research is used, the object in this study is learning Nahwu Sharaf with the Amtsilati method. The results of this study indicate that learning nahwu shorf by using the amtsilati method showed the time efficiency represents the problem in Nahwu-Sharaf learning. In terms of understanding, this method is mainly faster because the book uses the Indonesian language